Analisis Strategi Bisnis pada Kedai Kopi Aceh Kuphi Medan - Sari Mariahma Nova Sipayung (Fakultas Bisnis Universitas Mikroskil, 2021)
Coffee is one of the drinks that many people use to relax. Coffee shop is one of places to enjoy it. Aceh Kuphi is one of coffee shops in Medan city whose main product is coffee drinks from Aceh Gayo. The purpose of this research is to identify and analyze existing business strategies at the Aceh Kuphi coffee shop. This study uses a qualitative research type with a descriptive approach and the sampling uses purposive sampling. The research method used is a qualitative descriptive analysis method with SWOT analysis. The data collection techniques used were in-depth interviews, observation, and documentation. The result show that Aceh Kuphi coffee shop is in quadrant 1, where the coffee shop is in a very profitable situation. The recommended strategy from these quadrant is the Progressive strategy. The results of the SWOT matrix obtained an SO strategy with developing a marketing strategy using technology. WO strategy can maximize online media to promote products, ST strategy to maintain product quality and service quality to create customer loyalty and WT strategy to maintain price.